Perbedaan Struktur Kepemilikan, Ukuran Perusahaan, Dan Pembayaran Pajak Terhadap Manajemen Laba Sebelum Dan Saat Pandemi Covid19 (Studi Kasus Pada BUMDES Desa Ngroto Kec. Pujon Kab. Malang Tahun 2017 – 2022) - Afifah Afifah; Jeni Susyanti; Etty Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research was conducted in Malang Regency. The type of research used is explanatory research with a quantitive approach. The purpose of this study was to determine the effect of ownership structure, company size, tax payments, earnings management. The independent variables used are ownership structure, company size, and tax payments, while the dependent variable is the earnings management. The sample used in this study was 3 years before Covid-19 and 3 years when Pandemic Covid19 in Malang district. Data collection techniques using direct requests to the Bumdes. The analytical method used is paired sample t – Test using IBM SPSS 26 computer software for data processing. The results of this study indicate that there is no significant difference for ownership structure, while for the variable of company size and tax payments there is significant difference between before and when Covid-19.Keywords: Ownership Structure, Company Size, Tax Payments, Earnings Management